(untitled) (Maneggio, 2025)
This study aims to analyze To obtain information on whether there is a positive and significant influence of partial pricing strategies on room occupancy rates at the Niagara Hotel Parapat. The method used in this study is quantitative descriptive with a purposive sampling technique. The analysis tool used is multiple linear regression. From this study, it is known that from 45 respondents who answered the questionnaire with the results of the study, it was obtained that price has a significant effect on hotel room occupancy rates. This can be seen from the calculated t-value of 5.536 which is greater than the t-table value of 2.022 at a significance level of 5%. Thus, the hypothesis stating that price has an effect on room occupancy rates is accepted. Promotion has a significant effect on hotel room occupancy rates. This can be seen from the calculated t-value of 2.287 which is greater than the t-table value of 2.022 at a significance level of 5%. Thus, the hypothesis stating that promotion has an effect on room occupancy rates can be accepted. Price and promotion have a simultaneous effect on hotel room occupancy rates. This is evident from the significance value (Sig) of 0.000, which is lower than the significance level (α) of 0.05. Thus, the hypothesis that price and promotion jointly influence room occupancy rates is accepted.